What is known about Indigenous women’s dissatisfaction of Birthing experiences in mainstream maternity hospitals in Australia, Aotearoa, Canada, US, Kalaallit Nunaat and Sápmi? A systematic scoping review - Sivertsen, Nina; Johnson, Tahlia; Mehus, Grete; Ness, Tove Synnøve Mentsen; Smith, Susan; McGill, Josephine (Frontiers in Public Health, 2025)
IntroductionUnderstanding Indigenous women’s dissatisfaction with birthing experiences is vital for improving maternal healthcare. It highlights the need for compassionate, respectful care that meets women’s physical and emotional needs. Addressing these concerns can enhance patient satisfaction, reduce postpartum mental health issues and wellness, and ensure safer, more positive outcomes for mothers and babies.ObjectivesThis scoping review aimed to identify what is known about Indigenous women’s dissatisfaction of birthing experiences in mainstream maternity hospitals.Inclusion criteriaThis review considered primary research studies that reported on reasons for dissatisfaction of birthing experiences, and strategies implemented to improve quality of clinical practice around women’s dissatisfaction of birthing experiences in mainstream maternity hospitals in Australia, Aotearoa, Canada, US, Kalaallit Nunaat and Sápmi.FindingsA total of 22 manuscripts reporting 22 studies met the inclusion criteria and were included in the synthesis.DiscussionThere is a need for culturally safe trauma informed care, inclusive communication, active decision-making involvement and greater inclusion of Indigenous perspectives in maternity care, including the involvement of Indigenous birth support workers where appropriate and inclusion of Birthing on Country models of care.ConclusionThis review reveals that the medicalisation and evacuation of Indigenous women for childbirth cause cultural, geographic, and social disconnection, despite infant safety benefits. It underscores the need for better cultural safety education, communication, and the inclusion of cultural practices in care, with support from Indigenous birth support workers being essential.